Reversible luminescence switching of a redox-active ferrocene-europium dyad. - Tropiano, M; Kilah, N; Morten, M; Rahman, H; Davis, J; Beer, P; Faulkner, S (2011)
The copper-catalyzed cycloaddition reaction between a propargyl-appended europium complex and azidomethylferrocene yields a d-f dyad whose photophysical properties can be reversibly switched by varying the oxidation state of the ferrocene chromophore.